Decision‐making in the referral process of sonographers in primary care screening centers†. (17th May 2016) - Oosterhuis, Jolande J.; Gillissen, Ada; Snijder, Claudia A.; Stiggelbout, Anne; Haak, Monique C.
Abstract: Objectives: To explore the decision‐making process (whether or not to refer) of sonographers performing the 20 weeks standard anomaly scan (SAS) in the screening setting. Methods: A survey was sent to SAS‐sonographers; it assessed experience, training, volume, type of practice, perceived difficulty per organ system, feelings after missing anomalies and reasons for uncertainty and doubt concerning referral. Results: The response rate was 50%. Sonographers tend to seek reasons for uncertainty in patient factors and not in their skills or difficulty of the scan. Most mentioned reasons to refer in case of doubt were repeated visualization of a possible abnormality (98%). We hypothesize that the need of repeated imaging of an abnormality might partly explain why some fetal anomalies are still being missed. Sonographers with limited experience and low volume SAS more often revised, referred and asked colleagues for help than experienced sonographers with high volume SAS. In cases of a missed diagnosis, sonographers frequently blamed internal factors (personal failure 71%). Conclusion: Level of experience and volume of SAS influence revision and referral rates. Personal factors seem to play a role in the decision‐making process of screening sonographers. Future research should focus on these personal factors, to optimize screening ultrasound programs. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? In the Netherlands, ultrasound screening is performed by sonographers who decide which cases should be referred for prenatal diagnosis at referral centers. The criteria used by screening sonographers to make such decisions have never been explored in obstetrics. What Does This Study Add? It offers insight in the decision‐making process of sonographers whether or not to refer a case to a center for prenatal diagnosis. This may give an opportunity to improve training of sonographers which may ultimately lead to improved detection rates of the 20‐week anomaly scan.